2004
DOI: 10.2172/15020761
|View full text |Cite
|
Sign up to set email alerts
|

Hanford Tanks 241-C-203 and 241-C-204: Residual Waste Contaminant Release Model and Supporting Data

Abstract: This report describes the development of release models for key contaminants that are present in residual sludge remaining after closure of Hanford Tanks 241-C-203 (C-203) and 241-C-204 (C-204). The release models were developed from data generated by laboratory characterization and testing of samples from these two tanks. Key results from this work are that future releases from the tanks of the primary contaminants of concern ( 99 Tc and 238 U) can be represented by relatively simple solubility relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…On the other hand, the extraction results for both Fe and Al in the C-204 samples are generally consistent with their existence as relatively insoluble phases such as oxides; however, a surprisingly large amount of the Al (16%) dissolved during the deionized water extractions. This suggests that some Al exists in a relatively soluble phase, such as dawsonite [NaAlCO 3 (OH) 2 ] which has been observed in other residual tank sludges ( , ). However, the results of the C-204 characterization studies ( , ) do not provide any evidence for the presence of this phase.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…On the other hand, the extraction results for both Fe and Al in the C-204 samples are generally consistent with their existence as relatively insoluble phases such as oxides; however, a surprisingly large amount of the Al (16%) dissolved during the deionized water extractions. This suggests that some Al exists in a relatively soluble phase, such as dawsonite [NaAlCO 3 (OH) 2 ] which has been observed in other residual tank sludges ( , ). However, the results of the C-204 characterization studies ( , ) do not provide any evidence for the presence of this phase.…”
Section: Resultsmentioning
confidence: 88%
“…This suggests that some Al exists in a relatively soluble phase, such as dawsonite [NaAlCO 3 (OH) 2 ] which has been observed in other residual tank sludges ( , ). However, the results of the C-204 characterization studies ( , ) do not provide any evidence for the presence of this phase. The solid-phase characteriza tion studies ( , ) did identify a Na−Al−P−O±H phase; however, most phosphate solids are not expected to be significantly soluble under these conditions.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…A study was carried out by Deutsch et al [27] from the Pacific Northwest National Laboratory on the leaching of Tc-99 and dissolution of other chemical and radioactive species from solid residual waste sampled from C-203 and C-204. These studies revealed that there is a highly soluble form of technetium (pertechnetate) and an insoluble and inaccessible form of technetium in the particles.…”
Section: Leaching Tests On C-203 C-204 and C-106 Residual Wastementioning
confidence: 99%
“…Since these samples were taken in 2003 prior to waste removal from the tanks, the highly soluble pertechnetate had yet to be removed in the washing/removal process. Deutsch et al [27] suggest that the intractable technetium is incorporated into a very insoluble iron mineral, assumed to be ferrihydrite [Fe(OH) 3 ].…”
Section: Leaching Tests On C-203 C-204 and C-106 Residual Wastementioning
confidence: 99%